Magnetoliposomes Based on Shape Anisotropic Calcium/Magnesium Ferrite Nanoparticles as Nanocarriers for Doxorubicin - Beatriz D. Cardoso; Ana Rita O. Rodrigues; Manuel Bañobre-López; Bernardo G. Almeida; Carlos O. Amorim; Vítor S. Amaral; Paulo J. G. Coutinho; Elisabete M. S. Castanheira (MDPI AG, 2021)
Multifunctional lipid nanocarriers are a promising therapeutic approach for controlled drug release in cancer therapy. Combining the widely used liposome structure with magnetic nanoparticles in magnetoliposomes allies, the advantages of using liposomes include the possibility to magnetically guide, selectively accumulate, and magnetically control the release of drugs on target. The effectiveness of these nanosystems is intrinsically related to the individual characteristics of the two main components-lipid formulation and magnetic nanoparticles-and their physicochemical combination. Herein, shape-anisotropic calcium-substituted magnesium ferrite nanoparticles (Ca0.25Mg0.75Fe2O4) were prepared for the first time, improving the magnetic properties of spherical counterparts. The nanoparticles revealed a superparamagnetic behavior, high saturation magnetization (50.07 emu/g at 300 K), and a large heating capacity. Furthermore, a new method for the synthesis of solid magnetoliposomes (SMLs) was developed to enhance their magnetic response. The manufacturing technicalities were optimized with different lipid compositions (DPPC, DPPC/Ch, and DPPC/DSPE-PEG) originating nanosystems with optimal sizes for biomedical applications (around or below 150 nm) and low polydispersity index. The high encapsulation efficiency of doxorubicin in these magnetoliposomes was proven, as well as the ability of the drug-loaded nanosystems to interact with cell membrane models and release DOX by fusion. SMLs revealed to reduce doxorubicin interaction with human serum albumin, contributing to a prolonged bioavailability of the drug upon systemic administration. Finally, the drug release kinetic assays revealed a preferable DOX release at hyperthermia temperatures (42 °C) and acidic conditions (pH = 5.5), indicating them as promising controlled release nanocarriers by either internal (pH) and external (alternate magnetic field) stimuli in cancer therapy.